THE COMPABILITY OF TEACHING MEDIA WITH JAPANESE LANGUAGE MATERIALS OF GRADE XI SMA NEGERI 1 PADANGAN - Khoiruna, Annisaa Al; Supriatnaningsih, Rina; Rosliyah, Yuyun (Chi'e: Journal of Japanese Learning and Teaching, 2017)
Teaching media have to prepare ahead learning activity, since it is a teaching aid. Beside, the use of it has to be considered the materials which will be taught. In the introduction study, which interviews with the students and Japanese teachers were done, it had been found out that there were many students who had difficulties in understanding the materials. One of the reasons was that the teaching media used by the teachers was incompatible with the materials being taught; they often used Powerpoint as the media to deliver the materials. According to the explanation above, research problems in this study were (i) what media used in teaching Japanese activity in SMA Negeri 1 Padangan Grade XI (ii) is the use of the media compatible with the teaching materials. The goals of the study were to (i) describe media used in teaching Japanese activity in SMA Negeri 1 Padangan Grade XI (ii) describe the compatibility of the use of the media with the teaching materials. Quantitative and qualitative descriptive researches were used in this study. The variable of the study was the compatibility of teaching media with the Japanese language materials used by students in SMA Negeri 1 Padangan Grade XI. The data were collected through questionnaire, observation,  and documentation. Percentage descriptive analysis method was used to analyze the research data. The result showed that from 4 materials, chapter 2, chapter 3, chapter 4 and chapter 5, the teaching media used in delivering those first 3 chapters were compatible, while the teaching media used in the last chapter had not been compatible. Those teaching media used were picture cards, cassette/CD, PowerPoint and things around the students. Picture cards used in teaching chapter 2 かいてください(Kaite kudasai) was compatible with the materials.  Picture cards and PowerPoint uses in teaching chapter 3 わたしはBeno です(Watashi wa Beno desu) was compatible with the materials. Picture cards and PowerPoint uses in teaching chapter 4 でんわばんごう(Denwa bangou) was compatible with the materials. PowerPoint and real things around them used in teaching chapter 5 これはわたしのかさです(Kore wa watashi no kasa desu) were not compatible with the materials.